A Environmental Education Strategies @kebunkumara Instagram Social Media for Healthy Chicken Coops - Hidayatillah, Arifah Nurul; Subkhi Ridho (Jogjakarta Communication Conference (JCC), 2024)
This study aims to explore environmental education strategies used by @kebunkumara Instagram social media accounts in the context of promoting healthy chicken coops. A healthy chicken coop is very important for maintaining the health of chickens and producing quality products. Instagram social media can be an effective platform to spread information about healthy chicken coops. The @kebunkumara account is active in sharing information about healthy chicken coops on Instagram. Using qualitative approaches and case studies, this study analyzes various communication strategies applied by @kebunkumara to educate its audience about the importance of a healthy environment in the context of a chicken coop. Through content analysis, user interaction, and interviews with account owners, the study also evaluated the effectiveness of these strategies in raising awareness and understanding of environmental and animal welfare issues among Instagram audiences. This research shows that @kebunkumara use several communication strategies in disseminating information about healthy chicken coops, including: informative and educational content, attractive visuals, interaction with followers, cooperation with influencers. @kebunkumara use effective communication strategies in spreading information about healthy chicken coops on Instagram. This strategy can be an example for other chicken farmers who want to use social media for education about healthy chicken coops.